The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations KEEP THE SINK CLEAN Wash the sink out well after cleaning greasy cooking utensils. A little boiling water poured down the drain after washing up will prevent the sink being blocked. SEE THAT YOU KNOW WHERE YOUR STOP TAP IS In case of frozen or burst pipes, turn the water off at the stop tap, so do not fail to ascertain where this is situated. If water is running through an overflow pipe, inform the Estate Manager and until a repair is effected use the stop tap to prevent waste, turning it on from time to time as you need water. Do not draw off any hot water until repair has been effected. ACCIDENTS IN THE KITCHEN Most home accidents happen in the kitchen. Small children should not be allowed to play there unattended. See that the floor is even and the linoleum without holes in which folk may trip. Care may prevent most accidents, and cleanliness may prevent small accidents from causing blood poisoning. Good lighting helps to prevent accidents. MAKE SURE YOUR FOOD IS CLEAN AND SAFE It is best to buy fresh food. But in order to store what is left over and to keep the milk in good condition, there should be a refrigerator in every house. Refrigerators were at one time considered to be a luxury for the few, but prices both for the equipment and the current consumed are constantly decreasing and their use should be general. When you have a good refrigerator, you do not need a larder, unless you have a large amount of food to store. [illustration] A modern refrigerator. 10 177/5/8/2